Primary HSV-2 Infection in Early Pregnancy Results in Transplacental Viral Transmission and Dose-Dependent Adverse Pregnancy Outcomes in a Novel Mouse Model - Allison M. Felker; Philip Nguyen; Charu Kaushic (Viruses, 2021)
Herpes simplex virus type 2 (HSV-2) infection affects 24 million births annually and is associated with adverse pregnancy outcomes, including neonatal herpes; however, the mechanisms underlying in utero transmission of HSV-2 are largely unknown. We examined the effects of primary HSV-2 infection during early pregnancy on gestational outcomes in a novel, clinically relevant mouse model. Pregnant C57BL/6 mice were infected intravaginally with 102–105 pfu/mL HSV-2 on gestation day (gd) 4.5. Controls were infected, nonpregnant, diestrus-staged mice and pregnant, uninfected mice. Compared to nonpregnant mice, pregnant mice were 100-fold more susceptible to HSV-2 infection. Three days post-inoculation (gd7.5), viral DNA was present in implantation sites, but pregnancy outcomes were largely unaffected by infection. Eight days post-inoculation (gd12.5), HSV-2 DNA persisted in placental tissues, resulting in inflammation and hemorrhage. Fetal and placental weights were reduced and fetal loss was observed with high viral doses. HSV-2 DNA and increased expression of pro-inflammatory mediators were detected in fetal tissues at gd12.5, signifying viral transmission and fetal infection, even with low viral doses. This mouse model shows a dose-dependent effect of primary HSV-2 infection on pregnancy outcomes and suggests that fetal loss may occur due to placental inflammation, thus providing valuable insight into in utero transmission of HSV-2.